Deaf in AI: AI language technologies and the erosion of linguistic rig hts - De Meulder, Maartje (2025)
This paper explores the interplay of AI language technologies, sign la nguage interpreting, and linguistic access, highlighting the complex i nterdependencies shaping access frameworks and the tradeoffs these tec hnologies bring. While AI tools promise innovation, they also perpetua te biases, reinforce technoableism, and deepen inequalities through sy stemic and design flaws. The historical and contemporary privileging o f sign language interpreting as the dominant access model, and the bro ader inclusion ideologies it reflects, shape AIs development and deplo yment, often sidelining deaf languaging practices and introducing new forms of linguistic subordination to technology. Drawing on Deaf Studi es, Sign Language Interpreting Studies, and crip technoscience, this p aper critiques the framing of AI as a substitute for interpreters and examines its implications for access hierarchies. It calls for deaf-le d approaches to foster AI systems that remain equitable, inclusive, an d trustworthy, supporting rather than undermining linguistic autonomy and contributing to deaf aligned futures.
Keywords: Computer Science - Computers and Society